Tunable microwave absorption properties of nickel-carbon nanofibers prepared by electrospinning. Issue 3 (15th February 2019) - Shen, Yongqian; Wei, Yupeng; Ma, Jiqiang; Li, Qinglin; Li, Jian; Shao, Wenjie; Yan, Pengze; Huang, Guowei; Du, Xueyan
Abstract: The nickel-carbon nanofibers (Ni-C NFs) were fabricated by the electrospinning of poly(vinyl alcohol) (PVA) and nickel acetate tetrahydrate (NiAc) solution precursor with succedent PVA pyrolyzation and calcination process. The microwave absorption performance and electromagnetic (EM) parameters of the NFs were researched over the frequency range of 2.0–18.0 GHz. Both the impedance matching and EM wave absorption properties of the Ni-C NFs were improved by changing the carbonization temperature. The effect of graphitization degree on reflection loss (RL) and the possible loss mechanisms were directly displayed in the comparative study of each sample. The optimal RL value of − 44.9 dB and an effective frequency bandwidth of 3.0 GHz under a thickness of 3.0 mm can be reached by a sample calcined at 650 °C. These lightweight Ni-C NFs composites can be promising candidates for EM wave absorbers due to the combination of multiple loss mechanisms, nano-size effect and good impedance matching between Ni nanoparticles and CNFs.